Experimental infection of non-immunosuppressed and immunosuppressed goats reveals differential pathogenesis of Babesia aktasi n. sp. - Ozubek, Sezayi; Ulucesme, Mehmet Can; Bastos, Reginaldo G.; Alzan, Heba F.; Laughery, Jacob M.; Suarez, Carlos E.; Aktas, Munir (Frontiers Media Sa, 2023)
Babesiosis is an acute and persistent tick-borne disease caused by protozoan parasites of the genus Babesia. These hemoparasites affect vertebrates globally, resulting in symptoms such as high fever, anemia, jaundice, and even death. Advancements in molecular parasitology revealed new Babesia species/genotypes affecting sheep and goats, including Babesia aktasi n. sp., which is highly prevalent in goats from Turkiye's Mediterranean region. The objective of this study was to investigate the pathogenesis of B. aktasi infection in immunosuppressed (n=7) and non-immunosuppressed (n=6) goats. These animals were experimentally infected with fresh B. aktasi infected blood, and their clinical signs, hematological and serum biochemical parameters were monitored throughout the infection. The presence of parasites in the blood of immunosuppressed goats was detected by microscopic examination between 4 and 6 days after infection, accompanied by fever and increasing parasitemia. Goats that succumbed acute disease exhibited severe clinical signs, such as anemia, hemoglobinuria, and loss of appetite. However, the goats that survived showed milder clinical signs. In the non-immunosuppressed group, piroplasm forms of B. aktasi were observed in the blood within 2-5 days after inoculation, but with low (0.01-0.2%) parasitemia. Although these goats showed loss of appetite, typical signs of babesiosis were absent except for increased body temperature. Hematological analysis revealed significant decreases in the levels of red blood cells, leukocytes and platelet values post-infection in immunosuppressed goats, while no significant hematological changes were observed in non-immunosuppressed goats. In addition, serum biochemical analysis showed elevated transaminase liver enzymes levels, decreased glucose, and lower total protein values in the immunosuppressed group post-infection. Babesia aktasi, caused mild disease with minor clinical symptoms in non-immunosuppressed goats. However, in immunosuppressed goats, it exhibited remarkable pathogenicity, leading to severe clinical infections and death. In conclusion, this study provides valuable insights into the pathogenicity of the parasite and will serve as a foundation for future research aimed at developing effective prevention and control strategies against babesiosis in small ruminants. Further research is required to investigate the pathogenicity of B. aktasi in various goat breeds, other potential hosts, the vector ticks involved, and its presence in natural reservoirs.
Keywords: Babesia aktasi n. sp.; experimental infection; goat; immunosuppression; pathogenicity